Institutional delivery and its associated factors: A community based cross-sectional study in Kavre district - Shrestha, Sushila; Shrestha, Geeta Kamal (Journal of Kathmandu Medical College, 2017)
Background: Health facility delivery is considered a critical strategy to improve maternal health. The Government of Nepal is promoting institutional delivery through different incentive programs and the establishment of birthing centers. The objective of this study was to identify utilization of institutional delivery and its associated factors. Method: A descriptive cross-sectional study was carried out among the mothers of under five children in Dhungkharka. Pre-tested questionnaire was administered to 170 mothers between 15-45 years of age group. Household survey was done by using purposive sampling technique and face to face interview technique was used to collect the data from 1st Julyto 30 th December 2014. Data was analyzed using simple descriptive statistic with SPSS version 16. Association with institutional delivery was assessed by using chi-square test. Results: Among the total participants, 90.0% of them had institutional delivery. The higher proportions of institutional delivery were found in both literate mothers (p=0.001), and literate husband (p=0.023). The proportion of institutional delivery among the mothers decided by their relatives (husband, father/mother-in-laws and other family members) for institutional delivery had higher portion (p=0.048) of institutional delivery than participants who decide themselves. Conclusion: Utilization of institutional delivery was much higher than national figure. Institutional delivery was associated with both educational status of mothers and their husband. Decision made by husband, mother in-law, father in-law and other family members were also associated with institutional delivery. So, to increase institutional delivery, family members need to be encouraged for safe motherhood program. Journal of Kathmandu Medical College Vol. 6, No. 1, 2017, page: 22-26